Compilation of Quranic Verses Related To Visual Function - Badarudin, Noor Ezailina; Yazid, Yazlin; Md Halim, Siti Aishah Binti; Mohammad, Hasbullah (IIUM Medical Journal Malaysia, 2018)
Islam provides a comprehensive way of life where the revelations bestowed by Allah from the Quran and Hadith cover all aspects that leads to a well-balanced life. This study compiles all the Quranic verses related to visual functions which may serve as a reference for Muslims as well as non-Muslim primary eye care practitioners during their patients’ treatment and consultation. A website named “Search Truth” on http://www.searchtruth.com/was used as a tool to identify the Quranic verses related to visual function by typing in the keywords “eye/eyes”, “see”, “light”, “sight” and “vision” in the search boxes provided in the website. The program embedded in the website then listed the Quranic verses based on their English translation containing the respective keywords. The listed Quranic verses and their translations were verified manually using the Holy Quran Tafseer. The frequency of Quranic verses for each chosen keyword was determined. There were 34 Quranic verses related to visual function and could be explained scientifically. The frequency of Quranic verses related to visual function under the classification of “eye/eyes”, “light”, “see”, “sight” and “vision” were 15, 8, 3, 7 and 1 respectively. The fundamentals of visual functions may be explained scientifically based on the Quranic verses.